Calon Tunggal dalam Pemilihan Kepala Daerah di Indonesia: Perspektif Demokrasi dan Kinerja Partai Politik - Prioni Rahmanda Saputri; Yola Safitri; Imam Hakiki (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to answer two questions. First, why were there only single candidates in 37 regions in the 2024 simultaneous regional elections? Second, what are the risks of single candidates to democracy and the performance of political parties? The methods used are normative juridical methods with a legislative and conceptual approach. The research focuses on the phenomenon of single candidates in regional elections and its impact on democracy and the performance of political parties in Indonesia. The results of this study show that the phenomenon of single candidates in regional elections indicates weak local democracy and poor performance of political parties in carrying out their functions of regeneration and leadership recruitment. Elite domination, high political costs, and the strong influence of oligarchs make the nomination process non-competitive and reduce the space for alternative candidates. As a result, regional elections are only procedural without substance, widening the democratic deficit and opening space for local bossism and unhealthy power consolidation. If this condition continues, local democracy will move further away from the principles of openness, accountability, and fair competition.